Retaining tourism lifestyle entrepreneurs for destination competitiveness - Dias, Á. (2021)
Due to their representativeness in the universe of tourism businesses and the potential to generate innovation, tourism lifestyle entrepreneurs (TLEs) play an essential role in the competitiveness of tourism destinations. Despite this vital importance, the antecedents of innovation generated by these entrepreneurs and their willingness to stay at the destination are still under-explored. Findings from a survey of 178 TLEs indicate that the context influences community attachment, and affects indirectly innovation and willingness to stay. Community attachment has a positive influence on entrepreneurial self-efficacy, innovation and willingness to stay. A transition of the context results to developing economies was also taken into consideration. Theoretical and practical implications are discussed.